Love Affair Reflected At Henrik Ibsen's Hedda Gabler Play(1890); An Individual Psychological Approach - Primadani, Maya Berlian; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S., M.Hum (2015)
The major problem of this study is how love affair is reflected in Henrik Ibsen's Hedda Gabler. The objective if this study is to analyze the play based on the individual psychological analysis. In analyzing Hedda Gabler, the writer uses qualitative method and individual psychological approach. The data sources consist of primary data and secondary data sources. The primary data source is the Hedda Gabler play itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and individual psychologist. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The result of the study shows the following conclusion. Based on Individual Psychological Approach, Hedda Gabler play shows love affair happens in Hedda as the major character in this play.